Soil and weed management for enhancing arbuscular mycorrhiza colonization of wheat. (1st August 2013) - Brito, I.; Carvalho, M.; Goss, M. J.
Abstract Tillage and weed control are critical components of cropping systems that need to be combined such that crops benefit from reduced competition. However, weeds may also contribute to the biological diversity within the agro‐environment. This greenhouse study investigated whether common weeds of arable cropping systems were suitable host plants for arbuscular mycorrhizal fungi (AMF), allowing the development of extraradical mycelium (ERM) that can contribute to the early colonization of a following wheat crop, especially in the absence of soil disturbance. Weeds were allowed to grow for up to 2 months before being controlled by soil disturbance or herbicide application (glyphosate or paraquat). Pregerminated wheat seeds were then planted. Chemical control of the weeds prior to sowing enhanced the early arbuscular mycorrhiza (AM) colonization rate of wheat roots, whereas mechanical disturbance was less acceptable as a method of weed control for rapid AM colonization. The type of herbicide (contact or systemic) had no impact on colonization of the wheat crop. Enhanced AM colonization promoted early P acquisition and growth of the crop. Appropriate management of weeds emerging between two consecutive cropping seasons coupled with no‐till soil management could ensure a quick and efficient AM colonization of the following wheat plants.